1951
DOI: 10.1037/h0055726
|View full text |Cite
|
Sign up to set email alerts
|

The relation of sex, age and school achievement to levels of aspiration.

Abstract: The principal purpose of the present study was to discover to what extent there are sex differences in level of aspiration. Previous studies have indicated that sex differences may occur, but the data are in some cases ambiguous. The influence of other factors has not been investigated sufficiently, and therefore differences in age and scholastic achievement have been taken into account in the present study. METHODThe measuring instrument used in this study was comparable in all essential respects to the 'aspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

1955
1955
1984
1984

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
4
1
Order By: Relevance
“…This relationship has been reported by several others (Anderson & Brandt, 1939;Muthayya, 1963;Summer & Johnson, 1949). Those who have not found a relationship between achievement and goal setting have used experimental tasks that are unrelated to school performance (Red, McCary, & Johnson, 1962;Walter & Marzolf, 1951).…”
supporting
confidence: 57%
“…This relationship has been reported by several others (Anderson & Brandt, 1939;Muthayya, 1963;Summer & Johnson, 1949). Those who have not found a relationship between achievement and goal setting have used experimental tasks that are unrelated to school performance (Red, McCary, & Johnson, 1962;Walter & Marzolf, 1951).…”
supporting
confidence: 57%
“…Furthermore, Rosen (1956) found that children from the upper social strata have a need for higher achievement scores; a need which we feel probably stems from parental pressures and examples. In confirmation of this point, it seems to us, is the research finding which indicates that boys have higher achievement drives (levels of aspiration) than girls (Walter & Marzolf, 1951 ). A t first glance, there may seem to be a contradiction between the findings of McClelland, Merrill, and Rosen and the thesis of this paper.…”
contrasting
confidence: 40%
“…Some researchers have failed to mention the sex of the subjects (Crandall, Solomon, & Kellaway, 1961), and some have used only one sex of subjects (Crandall, Good, & Crandall, 1964;Diggory & Morlock, 1964;Feather, 1966;Locke & Bryan, 1966;Zajonc & Brickman, 1969). Nevertheless, there are researchers who contend with the issue of sex differences in expectancy statements (Bardwell, 1976;Bigelow, 1982;Clifford, 1975;Dweck, Davidson, Nelson, & Enna, 1978;Parsons et al, 1982;Walter & Marzoff, 1951). Walter and Marzoff (1951) compared the goal discrepancy scores of 4th, 6th, 8th, and 12th grade boys and girls.…”
Section: The Development Of Expectationsmentioning
confidence: 99%
“…Nevertheless, there are researchers who contend with the issue of sex differences in expectancy statements (Bardwell, 1976;Bigelow, 1982;Clifford, 1975;Dweck, Davidson, Nelson, & Enna, 1978;Parsons et al, 1982;Walter & Marzoff, 1951). Walter and Marzoff (1951) compared the goal discrepancy scores of 4th, 6th, 8th, and 12th grade boys and girls. They found that boys had higher goal discrepancy scores (i.e., were more inaccurate) than girls.…”
Section: The Development Of Expectationsmentioning
confidence: 99%